Academic Procrastination of Masters of the University in the Conditions of the COVID-19 Pandemic (Journal of Educational Sciences, 2021)
The transformation of the educational process against the backdrop of the COVID-19 pandemic was accompanied by serious tension in society, a lack of skills in using online platforms for work and training, as well as technical limitations of Internet communication channels. The study of academic procrastina- tion of undergraduates against the background of self-isolation and the coronavirus pandemic is espe- cially relevant, since in this case procrastination is not associated with a lack of motivation or unwilling- ness to perform the required academic tasks. The purpose of the article is to investigate the manifestation of academic procrastination among undergraduates of the Al-Farabi Kazakh National University (KazNU) against the background of COVID-19 and the transition to a remote learning format.The article presents the results of a study of academic procrastination that has engulfed undergradu- ates in the context of a new format of distance learning in universities in the current circumstances of the COVID-19 pandemic. The study used a modification of the methodology “The Tuckman Procrastination Scale” and the methodology of K. Dweck (questionnaire of implicit theories). 72 KazNU undergraduates were examined, the following results were obtained – 50% of undergraduates showed a high level of procrastination according to B. Tukman’s method, 43% – average, 7% – low. According to further stu- dent interviews, the differences between undergraduates with low, medium and high levels of academic procrastination were studied. Undergraduates with a high level of academic procrastination during the COVID-19 pandemic perceived complex, large and insufficiently understandable tasks (lack of necessary information) as an argument to postpone or not start work at all. In addition, it turned out that most of them had relatives and friends who were sick at that time, as a result, they were frightened and confused. Identified digital factors influencing procrastination according to the questionnaire of implicit theories.Key words: procrastination, academic procrastination, procrastinator, undergraduates, COVID-19 pandemic.